The Implementation of SFAS 71, Bank Equity Valuation, and the Moderating Effect of Bank Size - Iman Sofian Suriawinata (The Indonesian Journal of Accounting Research, 2023)
This study is the first that investigates the value relevance of SFAS 71 within the banking sector, especially relating to the role of the new accounting standards in reducing the problem of information asymmetry due to bank asset opacity. Using samples consisting of 41 listed banking firms from 2016 to 2020, this study shows that the empirical relationship between the initial implementation of SFAS 71 and bank equity value is inverse U-shaped or concave and that bank size has a negative moderated effect on the relationship between the initial implementation of SFAS 71 and bank equity value. These findings indicate that: (i) at low levels of retained earnings adjustments due to the initial implementation of SFAS 71, the disclosure effect brought by the new accounting standards has a positive relationship with bank equity valuation, (ii) at higher levels of adjustments beyond those previously anticipated by capital market investors, the substantial effect of the new accounting standards has a negative relationship with bank equity valuation, and (iii)  larger banks have more opaque assets and therefore suffer more significant valuation discounts due to the substance effect